Enhancing Soil Nutritional Status in Smart Farming: The Role of IoT-Based Management for Meeting Plant Requirements - Nicky Oktav Fauziah; Betty Natalie Fitriatin; Hanif Fakhrurroja; Tualar Simarmata (International Journal of Agronomy)
Soil nutrition assessment is a critical factor in improving both the quantity and quality of agricultural yields. The integration of Internet of Things (IoT) technology represents a groundbreaking advancement, allowing for real-time measurements in smart farming. This article focuses on investigating and evaluating the current challenges in nutrient management within smart farming and explores the future potential of utilizing IoT for nutrient management. To gather data, bibliometric analysis and utilization of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart were conducted, searching on the Publish or Perish and Science direct search engines using the keywords “soil nutrient monitoring smart farming internet of things” without quotation marks. A total of 395 articles were initially identified, 20 of which were included in the analysis after verification with Covidence assessment tools. Our review of existing studies revealed that many nutritional management approaches are still in prototype and experimental design, without the use of experimental design agriculture standards, without validation through plant testing, and mainly focus on monitoring systems. This highlights the need for additional research into large-scale studies, considering data security and the application of this technology in agricultural experimental design across a wide range of agricultural practices. Furthermore, future research on NPK IoT-based sensors is expected to provide numerous benefits and accessibility to all farmers, ensuring agricultural profitability.